THUNDARR THE BARBARIAN. (From Abba to Zoom: A Pop Culture Encyclopedia of the Late 20th Century, 2005)
Information about "Thundarr the Barbarian," the science fictional animated television series, is presented. The series, which was aired on Saturday mornings from 1980-1982, featured ex-slave Thundarr, a blond Adonis-type who uses the Sun Sword to fight for justice on planet earth 2,000 years into the future.